2014
DOI: 10.1021/jo501127h
|View full text |Cite
|
Sign up to set email alerts
|

A Musclelike [2](2)Rotaxane: Synthesis, Performance, and Molecular Dynamics Simulations

Abstract: A novel bistable symmetric [2](2)rotaxane was prepared by a threading-followed-by-stoppering strategy and characterized with (1)H, (13)C, and 2D ROESY NMR spectroscopy and HR-ESI spectrometry. The symmetric [2](2)rotaxane system consists of an anthracene-based bis(crown ether) as macrocycles, and each of the two dibenzo[24]crown-8 (DB24C8) rings is threaded by the pendant substituents of a symmetrically substituted central rotatable ferrocene subunit that possesses two distinguishable recognition sites for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 57 publications
0
13
0
2
Order By: Relevance
“…It is notable that the DBA protons in [2]rotaxane 6 cannot be detected because there are no hydrogen bonding interactions between the crown ether and the DBA hydrogen atoms. 16 Compared with the 1 H NMR spectrum of hetero[4]rotaxane 5 , H 4 and H 5 which are adjacent to the DBA site were observed to shift upfield with a Δ δ of –0.53 ppm in the 1 H NMR spectrum of [2]rotaxane 6 , which confirmed that the DBA sites were not bound by the host macrocycle DB24C8 . Therefore, the phenyl-stopped B21C7 played an important role in inhibiting the dethreading of the daisy chain structure in the middle, this is also called a cascade-stopped strategy.…”
Section: Resultsmentioning
confidence: 80%
“…It is notable that the DBA protons in [2]rotaxane 6 cannot be detected because there are no hydrogen bonding interactions between the crown ether and the DBA hydrogen atoms. 16 Compared with the 1 H NMR spectrum of hetero[4]rotaxane 5 , H 4 and H 5 which are adjacent to the DBA site were observed to shift upfield with a Δ δ of –0.53 ppm in the 1 H NMR spectrum of [2]rotaxane 6 , which confirmed that the DBA sites were not bound by the host macrocycle DB24C8 . Therefore, the phenyl-stopped B21C7 played an important role in inhibiting the dethreading of the daisy chain structure in the middle, this is also called a cascade-stopped strategy.…”
Section: Resultsmentioning
confidence: 80%
“…In conclusion, a potential energy curve (PEC) was mapped for the acidbase switchable [2](2)rotaxane in its two protonation states. The original system must overcome a 10 kcal/mol barrier in order to switch to its other conformation; therefore, we propose a chemically modified system.…”
Section: Discussionmentioning
confidence: 99%
“…The similar operation of a bipodal molecular elevator with a ferrocene platform was also demonstrated by Qu. 68…”
Section: +mentioning
confidence: 99%